KALENDER ISLAM GLOBAL: PERSPEKTIF SYARIAH, EKONOMI, DAN POLITIK - Tono Saksono (JURIS (Jurnal Ilmiah Syariah), 2017)
Moslems all over the world should be able to make maximum use of united Islamic calendar as the follow up of the International Hijri Calendar Unity Congress in Istanbul on May 2016 in order to unite time management system of the Muslims. Rigid attitudes which reject hisab and only approved rukyatul hilal have made Muslims keep using Gregorian calendar for 1200 years as the basis of their business accounting. Consequently, Muslims seem to be trapped in zakat debts that keep getting more and more reaching US$ 10 bn. This will immediately become civilization debt and burden of the upcoming Muslim generation if it is not immediately solved.